Biochar-assisted nitrogen reduction improves resource efficiency at the expense of rice yield - Nowrose Jahan Lipi; Md. Harun-Or- Rashid; Swadesh Chandra Samanta; Muhammad Maniruzzaman; Md. Abdul Kader; Shamim Mia (Universitas Sebelas Maret, 2025)
Nitrogen (N) is the most essential nutrient element for improving crop yield. However, urea, its most common form, is highly prone to losses, especially in flooded rice fields, which reduces N use efficiency (NUE) and contributes to environmental degradation. Here, a field experiment was conducted to examine the yield and growth performance of Aman rice, as well as to estimate NUE using different organic amendments and inorganic N sources. The treatments consisted of two factors: a) organic amendments- waste biochar, sawdust biochar, cow dung, and control, and b) N application rate- control (0), 50%, and 100% of the recommended rate. Overall, waste biochar performed better than sawdust and cow dung. Waste biochar with 100% of the recommended rate of urea application provided the highest grain (4.65 t ha-1) and straw yield (6.72 t ha-1). However, waste biochar with 50% recommended urea application provided the best NUE, i.e., agronomic N use efficiency (46 kg rice grain kg-1 N applied), physiological N use efficiency (28 kg rice grain kg-1 N uptake), and apparent N recovery (61%). The relatively higher NUE in treatments with organic amendments and half the recommended N rate; suggests a trade-off between improved NUE and rice grain yield. The enhanced NUE was possibly manifested by retaining more N in the reactive sites of soil organic matter and its uptake in the plant. Altogether, our results provide insights into NUE in rice cultivation systems after application of diverse organic matters.